Cell‐specific diversity in the expression and organization of cytoplasmic plaque proteins of apical junctions. Issue 1 (15th June 2017) - Vasileva, Ekaterina; Sluysmans, Sophie; Bochaton‐Piallat, Marie‐Luce; Citi, Sandra
Abstract: Tight and adherens junctions play critical roles in the barrier, adhesion, and signaling functions of epithelial and endothelial cells. How the molecular organization of these junctions is tuned to the widely diverse physiological requirements of each tissue type is not well understood. Here, we address this question by examining the expression, localization, and interactions of major cytoplasmic plaque proteins of tight and adherens junctions in different cultured epithelial and endothelial cell lines. Immunoblotting and immunofluorescence analyses show that the expression profiles of cingulin, paracingulin, ZO‐1, ZO‐2, ZO‐3, PLEKHA7, afadin, PDZD11, p120‐catenin, and α‐catenin, as well as the transmembrane junctional proteins occludin, E‐cadherin, and VE‐cadherin, are significantly diverse when comparing kidney cells (MDCK, mCCD), keratinocytes (HaCaT), lung carcinoma (A427, A549), and endothelium‐derived cells (bEnd.3, meEC, H5V). Proximity ligation and co‐immunoprecipitation assays show that PLEKHA7 and PDZD11 are significantly more associated with the tight junction proteins cingulin and ZO‐1 in aortic endothelium–derived (meEC) cells but not kidney collecting duct epithelial (mCCD) cells. These results provide evidence that the cytoplasmic plaques of tight and adherens junctions are diverse in their composition and molecular architecture and establish a conceptual framework by which we can rationally address the mechanisms of tissue‐dependent junction physiology and signaling by cytoplasmic junctional proteins.